Mothers’ Perceptions of their Control over their Children’s Diets - Pettigrew, Simone; Roberts, M. (Association for Consumer Research, 2007)
In an era of rising rates of childhood obesity it is increasingly important for parents to ensure their children consume healthy diets. Given current trends in childhood obesity, it would appear that many parents are failing to engage in effective feeding practices. As mothers remain the major influence on family eating patterns (World Health Organisation (WHO) 2000), the extent to which they consider themselves to be in control their children's diets is important as it indicates where possible solutions to childhood obesity may lie. This paper explores the factors that mothers feel diminish their control over their children's diets to provide insight into why obesity is a growing problem in countries such as Australia despite the ready availability of low-energy nutritious foods and the good intentions of parents.